Serum peptide profiling: identifying novel cancer biomarkers for early disease detection - Martorella, Andrew; Robbins, Richard (Acta Biomedica Atenei Parmensis, 2007)
Recent advances in mass spectrometry have enabled the identification of hundreds of low molecular weight (LMW) peptides that have previously been difficult to detect in human serum. Serum peptide patterns can now be analyzed using commercially available statistical programs to identify potential peptide patterns that may correlate with the presence or absence of specific diseases. A serum peptide profile (SPP), which is unique to each patient, can be created and compared to a known SPP from a specific disease. The SPP thus serves as a potential early stage biomarker prior to the clinical manifestation of disease. A unique and automated technology platform has been developed by members of the Protein Center at Memorial Sloan-Kettering Cancer Center (MSKCC). It involves a magnetic bead-based approach to extract LMW peptides from serum, placing them by robotic automation on a stainless steel MALDI-TOF target plate, subjecting them to mass spectrometric analysis, and using GeneSpring software to analyze the peptide patterns. Human serum from a cohort of 27 patients with metastatic thyroid cancer and 32 controls were analyzed on the MSKCC platform. 549 individual LMW peptides were identified. A SPP composed of 98 discriminatory LMW peptides was able to distinguish between the two groups of serum samples with high statistical accuracy.We believe that our automated system will serve as a model for future biotechnology laboratories in the quest for hidden diagnostic clues that may be detected by simply analyzing a drop of blood.